The University of Amazon State (UEA) as a social, economic and environmental development in the triple amazon border (Research, Society and Development, 2022)
The study aims to analyze the history of the arrival of the University of Amazon State (UEA) in Tabatinga/BR, located on the border with Letícia/CO and Santa-Rosa/PE. We carried out bibliographic, documentary and field research and, due to the pandemic situation, we chose to use WhatsApp and Google Meet to carry out interviews. The thread of the search for higher education in Alto Solimões begins with the Rondon Project, which, together with the Pontifical Catholic University of Rio Grande do Sul (PUCRS,) took university students to do internships, serving the needy population. In 1989, with the extinction of the project, the social agents of the region started a movement for the University of Amazonas (UA) to extend its activities to the interior of the Amazon. In the year 2000 Tabatinga is contemplated to receive a Center of the UEA starting to reconfigure the lives of the residents and the relations in the environment of the triple Amazonian border. With the various social manifestations in favor of education in Tabatinga and Alto Solimões, there was the installation of the Center for Higher Studies in Tabatinga-CSTB, which ceased to be a utopia, as well as the implementation of courses aimed at teacher training, raising capital cultural and intellectual property of the border population. As a result, social relations are gradually being modified, reflecting a significant change in the quality of basic and higher education, giving rise to new needs that require other struggles.